Formulasi Dan Aktivitas Antioksidan Sediaan Masker Mata Hidrogel Dari Sari Umbi Wortel (Daucus Carota L.) - Nurhayati, Nina; Novi, Cory; Junaedi, Candra (PT. Pubsains Nur Cendekia, 2025)
Carrots (Daucus carota L.) are a root vegetable that contains high levels of antioxidants and can be used as a base ingredient in masks. Carrots contain antioxidants such as vitamin C and vitamin A, which can act as skin moisturizers. This study aims to develop a hydrogel eye mask formulation from carrot root extract and test its antioxidant activity using the 1,1-diphenyl-2-picrylhydrazil (DPPH) method. Carrot root extract was formulated into hydrogel eye mask preparations Basis, F1, and F2. Evaluation of the hydrogel eye mask preparations included organoleptic observation, storage stability test, adhesion test, pH test, and hydrogel eye mask shrinkage test. The results showed that the carrot root hydrogel eye masks had antioxidant activity with an average IC50 value of 1167.67 ppm for Basis, 163.63 ppm for F1, and 145.94 ppm for F2. The formulation of hydrogel eye masks from carrot root extract at concentrations of Basis, F1, and F2 had good properties, namely pH, storage stability, adhesion test, mask shrinkage, color, odor, and shape that met the requirements for topical preparations.